2006
DOI: 10.1126/science.1133197
|View full text |Cite
|
Sign up to set email alerts
|

Greater Disruption Due to Failure of Inhibitory Control on an Ambiguous Distractor

Abstract: Experiment 1 (RSVP task with translating dots) Main experimentA sequence of 8 items (2 digits and 6 letters [65.9cd/m 2 ]) were presented in a 1°diameter, dark-grey circle (28.8 cd/m 2 ) located within a 10° diameter, black circular background (0.2 cd/m 2 ). Each item (digit or letter) was presented for 75 msec and was

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
169
5

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 160 publications
(202 citation statements)
references
References 29 publications
28
169
5
Order By: Relevance
“…Several experimental results on attention and awareness have been interpreted as consistent with this prediction (McCormick, 1997;Tsushima et al, 2006;Lin and Murray, 2015;Webb and Graziano, 2015;Webb et al, 2016a), though more experiments are needed. Thus far, the relevant experiments have focused on visual attention and visual awareness.…”
Section: The Adaptive Value Of An Attention Schema: Control Of Attentionmentioning
confidence: 60%
See 1 more Smart Citation
“…Several experimental results on attention and awareness have been interpreted as consistent with this prediction (McCormick, 1997;Tsushima et al, 2006;Lin and Murray, 2015;Webb and Graziano, 2015;Webb et al, 2016a), though more experiments are needed. Thus far, the relevant experiments have focused on visual attention and visual awareness.…”
Section: The Adaptive Value Of An Attention Schema: Control Of Attentionmentioning
confidence: 60%
“…When people are unaware of a visual stimulus, they can still sometimes focus processing resources on it. They can direct attention to it (McCormick, 1997;Lamme, 2003;Woodman and Luck, 2003;Ansorge and Heumann, 2006;Tsushima et al, 2006;Kentridge et al, 2008;Hsieh et al, 2011;Norman et al, 2013). However, in that case, visual attention suffers deficits in control.…”
Section: The Adaptive Value Of An Attention Schema: Control Of Attentionmentioning
confidence: 99%
“…(cf. Tsushima et al 2006;Bahrami et al 2007;Chun and Marois 2002;Keller 2011;Marchetti 2012;Rees 2013;Baars 2013;Tsuchiya and van Boxtel 2013), the attention-based scaling item in the SynQ measurement inventory is highly provisional and further experimental disentanglement of relations between synaesthetic induction and endogenous attention/ concentration within the stimulus/response event will be needed (see Item #8 in Exhibit 1).…”
Section: Domains and Scale Value Identificationmentioning
confidence: 99%
“…(e.g. Zihl et al 1983;Vaina et al 1998;Tsushima et al 2006;Huxlin et al 2009;Furlan and Schwarzbach 2009) and hence we assume that groups of neurons within this area might respond to stimuli moving in a specified direction. 2 For the purpose of the simulations we considered eight groups or pools of neurons which respond when a substantial amount of dots move coherently into their preferred direction.…”
Section: General Setupmentioning
confidence: 99%
“…Furthermore, neuroimaging studies demonstrated that changes in cortical activations might accompany perceptual learning in general (e.g. and that attention modulates neuronal activities for different levels of motion coherence (Furlan and Schwarzbach 2009;Tsushima et al 2006). Recently Huxlin et al (2009) even demonstrated that motion discrimination might be relearned after damage to the primary visual cortex.…”
Section: Introductionmentioning
confidence: 99%